Pengaruh Brand Image terhadap Keputusan Pembelian pada Produk Wardah - Trimurti, Shari Cahya (Jurnal Psikologi Terapan, 2024)
Competition in the cosmetics industry is getting tighter with the presence of local and international products. Building a brand image is one indicator of the success of a product to compete in the market. This study aims to examine the influence of brand image on purchasing decisions of Wardah products. The subjects in the study consisted of 54 respondents obtained by sampling technique, namely purposive sampling. Data collection was carried out with a brand image scale based on Keller's dimensions (2013) and a purchasing decision scale based on Setiadi (2016). Data analysis carried out in this study was linear regression analysis. The results of this study showed an R value of 0.890, so there was a significant positive influence between brand image and purchasing decisions.